How Does Port Efficiency Affect Maritime Transport Costs and Trade? : Evidence from Indian and Western Pacific Ocean Countries - Herrera Dappe, Matias; Jooste, Charl; Suárez-Alemán, Ancor (World Bank, Washington, DC, 2017)
Would improvements in port performance increase trade in countries on the Indian and Western Pacific Oceans? Previous studies attempted to answer this question using ad hoc measures of port efficiency that do not control for the actual use of port assets or measures that can be very noisy. To avoid these problems, this paper builds a measure of economic efficiency based on the use of port inputs to deliver port output. Using data envelop analysis, it ranks countries on the Indian and Western Pacific Oceans in terms of their port efficiency, and assesses the effect of increased efficiency. It finds that becoming as efficient as the country with the most efficient port sector would reduce their average maritime transport costs by up to 14 percent and increase their exports by up to 2.2 percent.